TINDAK TUTUR ASERTIF DAN DIREKTIF PADA NOVEl "TAK PUTUS DIRUNDUNG MALANG" KARYA S. TAKDIR ALISJAHBANA - Asep Purwo Yudi Utomo; Alif Farkhatunnisa; Anisah Fitriyani (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2023)
This study aims to explain the form of assertive and directive speech in the novel "Tak Putus Dirundung Malang" by S. Destiny Alisjahbana, as well as to understand the meaning of each speech in the form of writing, especially in novels. The method used in this study is a qualitative descriptive method with a pragmatic approach. This research data is the speech of the characters in the novel "Tak Putus Dirundung Malang" by S. Destiny Alisjahbana. Then the collected data is analyzed based on the theoretical studies that have been obtained. From the results of the analysis, seven forms of assertive speech acts and seven forms of directive speech acts were obtained. Forms of assertive speech acts that have been found, namely assertive speech acts stating (8 quotes), bragging (3 quotes), complaining (7 quotes), expressing (8 quotes), expressing opinions (12 quotes), mentioning (2 quotes), and reporting (4 quotes). The forms of directive speech acts found, namely prohibitive directive speech acts (17 citations), commanding (20 citations), begging (4 citations), demanding (4 citations), advising (13 citations), advising (13 citations), suggesting (21 citations), and opposing (3 citations). So, it can be concluded that this novel contains many directive speech acts, especially in the form of speech that has the intention of suggesting and commanding.